Childhood Trauma and Cognitive Functioning: A Cross-Sectional Study of In-School Adolescents in Gwagwalada, Nigeria - Arogbofa, Anthony A. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Childhood trauma is a well-established risk factor for cognitive impairments; however, its impact on Nigerian adolescents remains underexplored. This study examined the relationship between childhood trauma and cognitive functioning among in-school adolescents in Gwagwalada, Nigeria. Employing a cross-sectional design, 240 students (120 males, 120 females; M = 14.5 years, SD = 1.47) were randomly selected from four secondary schools. Trauma exposure was measured using the Childhood Trauma Questionnaire (CTQ-28), while cognitive functioning—specifically memory, attention, and executive function—was assessed using the PROMIS Pediatric Item Bank v1.0. Results revealed that 75% of participants reported experiencing at least one form of trauma, with emotional abuse being the most prevalent (45%). Correlation and regression analyses showed a significant negative association between trauma exposure and cognitive functioning (r = –0.42, p < 0.01), with emotional abuse emerging as the strongest predictor (β = –0.35, p < 0.01). ANOVA results confirmed significant group differences, indicating that emotional abuse predicted the most severe cognitive deficits (F(4, 235) = 9.12, p < 0.01). Gender emerged as a moderating variable, with female adolescents exhibiting heightened vulnerability to trauma-related cognitive impairments. These findings underscore the critical need for trauma-informed educational and clinical interventions tailored to adolescent populations in Nigeria. The study recommends further research into the neurobiological pathways of trauma and the development of culturally responsive support systems for affected youth.